Malignant hyperthermia without fever in a burned child after bandaging: A case report - Arnildo Linck Júnior; Flávia Lopes Gabani; Mariana Moscardi Gaino; Jeová Moscardi Gaino Silva; Fabiano Mattos Urquisa (Elsevier, 2023)
During anesthetic procedures in pediatrics, especially when inhaled drugs or neuromuscular blockers are needed, adverse events related to the interaction of the pharmacological agent with the patient's sensitivity and susceptibility, such as malignant hyperthermia, are possible. Such a condition is considered an anesthetic emergency, requiring a high degree of diagnostic suspicion, a specific propaedeutic approach, and early and targeted treatment. Although rare, MH is relatively more prevalent among children, and in most cases, its diagnosis occurs during clinical signs such as localized or generalized hypertonia, hypercapnia, tachycardia, and fever. Nevertheless, many patients may not present hyperthermia during these events. In the following report, we describe the characteristics of a burn victim child who, during a bandaging procedure requiring anesthetic agents for induction, presented clinical manifestations during and after the surgical procedure compatible with the diagnosis of malignant hyperthermia but without fever, promptly treated with dantrolene, with satisfactory clinical and laboratory results. Increased sensitivity in the suspicion of drug-related complications may favor the early recognition of certain diseases and allow earlier therapy and favorable outcomes.